Annual report readability and stock liquidity. Issue 2 (5th March 2019) - Boubaker, Sabri; Gounopoulos, Dimitrios; Rjiba, Hatem
Abstract: We examine the effect of annual report textual complexity on firms' stock liquidity. Using techniques from computational linguistics, we predict and find that less readable filings are associated with lower stock liquidity. Our study provides evidence that difficult‐to‐read annual reports hinder investors' ability to process and analyze information contained in corporate annual reports, reducing thereby their willingness to trade which decreases stock liquidity. Our findings are robust to a battery of sensitivity tests, including endogeneity, use of alternative estimation techniques, and use of alternative liquidity and readability proxies.